Performance evaluation of geopolymer mortar with sustainable palm oil clinker sand using a volume based approach / Pouya Darvish - Pouya , Darvish (2021)
Excessive sand exploitation is believed to be one of the main factors for lowering groundwater and flooding, resulting in erosion. This research focused on replacing the conventional sand with a local industrial by-product, palm oil clinker (POC), to incorporate in mortar and concrete. The physical properties, chemical composition, and microscopic images of POC sand and conventional sand were compared. Due to POC’s porous nature and irregular shape, a volume-based approach was applied for replacements and to design mixes based on ASTM codes of practice. Fresh and hardened characteristics such as mechanical properties, durability, and microstructural investigations were performed in order to study the effect of POC in cement and geopolymer mortars and concrete. In addition, the effect of different gradings of POC sand was studied in both cases of cement and geopolymer mortars to have a better understanding of this by-product. To promote the sustainability of the geopolymer products, the mixes were cured at ambient condition to eliminate the unnecessary oven-curing method. This was possible with the incorporation of ground granulated blast-furnace slag (GGBS), which is a by-product of the iron mill. POC sand showed a comparable result in cement and geopolymer mortars to those of mining sand mortars. However, a slight decrease in the compressive strength was reported while benefiting from a lower density. It was found that the use of finer particles of POCS decreased the flowability while it increased the compressive strength. Furthermore, the sodium silicate present in the geopolymer was replaced with an identified batik waste generated from the batik factories with different percentages. With up to 60% replacement of commercial sodium silicate with batik waste, the 28-day compressive strength experienced a negligible reduction of less than 5% to achieve 65 MPa. The utilization of batik waste as the replacement for conventional commercial silicate demonstrated acceptable performance in geopolymer mortar and concrete. The incorporation of these waste materials in concrete could improve sustainability, reduce the cost, and mitigate the environmental impacts. To address the application of the findings, the materials and the concept were further deployed in concrete and the production of hollow blocks.